ASSESSING THE STUDENTS’ COMPREHENSION ON DESCRIPTIVE TEXT THROUGH RECOMBINATION AND APPROXIMATION STRATEGY - Ngatu, Simon P K (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2025)
The paper considers to assess whether recommendation and approximation are suited to beginners as well as intermediate and advance students in writing. The growing academic interest towards writing comprehension in language teaching leads every language teachers to find appropriate strategies to assess the students’ writing ability. Recombination and approximation are apparently known as two important strategies to assess the students’ ability in writing. The assessment itself covers content, grammatical accuracy, organization, and vocabulary along with its coherence and cohesion. The assessment of this study was based on discourse approach. The data collected from a private English course in Yogyakarta. Six students were randomly selected for the study, with two from each level participating. This study employed a combination of methods, including a writing test and a semi-structured interview. The results of the writing test were then subjected to a thorough analysis, employing analytical scoring rubrics as a methodological framework. The findings indicate that recombination is an appropriate learning strategy for novice students, while approximation is more suitable for intermediate and advanced students.